Akciğer tüberkülozlu hastalarda damgalanmanın değerlendirilmesi ; Evaluate the stigma on patients with tuberculosis - Açıkel, Günsel Yiğit (My University, 2013)
1.ÖZET (Akciğer tüberkülozlu hastalarda damgalanmanın değerlendirilmesi) Bu araştırma akciğer tüberkülozlu hastalarda damgalanmanın değerlendirilmesi amacıyla tanımlayıcı olarak yapıldı. Veriler yüz yüze görüşme yöntemiyle, Hasta Tanıtım Formu ve Tüberkülozlu Hastalarda Stigma Ölçeği (THSÖ) kullanılarak toplandı. Araştırmanın örneklemini Yalova Verem Savaş Dispanseri’ne başvuran ve çalışmayı kabul eden 105 hasta oluşturdu. Hastaların yaş ortalaması 42.14±17.31 yıl olup, %71.4’ü erkektir. Araştırmaya katılan hastaların cinsiyet, medeni durum, meslek, sosyal güvence, hastalık durumu ve tüberküloz nedeniyle hastaneye yatış durumlarına göre damgalanma durumları değişmediği görüldü. Son iki yıl içinde tüberküloz geçirenler ile tüberküloz olduğunu söylemeyenlerin toplam damgalanma puanları diğerlerinden daha yüksekti. Ailesinde tüberküloz olanlar içselleştirilmiş damgalanmayı daha fazla yaşarken, ilaçlarını bilerek aksatanların hissedilen damgalanma alt boyutunun yüksek olduğu görüldü. İlkokul mezunları ve ekonomik durumu orta olanların ise aile/ arkadaş ilişkilerinde daha fazla damgalanma yaşadığı bulundu. Buna göre; akciğer tüberkülozlu hastalar orta düzeyde damgalanma yaşamaktadır. Akciğer tüberkülozlu hastalarda damgalanmayı etkileyen faktörlerin sağlık çalışanları ile birlikte toplum tarafından da bilinmesi gereklidir. Akciğer tüberkülozu, damgalanma, tüberküloz 2.

Evaluate the Stigma on Patients with Tuberculosis This study was conducted to evaluate stigmatization for patients with pulmonary tuberculosis as descriptive. Data was collected using Patient Identification Form and Stigma Scale for Patients with Tuberculosis (SSPT) by face-to-face interview method. Sample of the study consisted of 150 patients applying to Yalova Tuberculosis Dispensary who accepted to participate in the study. Age average of patients was 42.14±17.31 years and 71.4% of them were male. It was found that stigmatization of patients participating in the study did not affected on gender, marital status, occupation, social security, sickness level and hospitalization conditions due to tuberculosis. Total stigmatization points of patients who suffered from tuberculosis in last two years and patients who did not tell that they had tuberculosis were higher than the others. While patients who had relatives with tuberculosis experienced more the interiorized stigmatization, sub dimension of stigmatization felt by patients who didn’t take their medication intentionally was higher. It was observed that primary school graduate and patient whose economic conditions had medium level experienced more stigmatization in their family/ friend relationships than the others. Accordingly, patients with pulmonary tuberculosis experienced medium level stigmatization. Factors which affect stigmatization for patients with pulmonary tuberculosis should be known by healthcare staff as well as the society. Key Words: Pulmonary tuberculosis, stigmatization, tuberculosis
Keywords: Akciğer Hastalıkları; Akçiğer Tüberkilozu; Hemşirelik; İç Hastalıkları